Development of an Off-Grid Photovoltaic (OGPV) System for Residential House Educational Kit - Hairei, Nur Liyana Balqis; Mohammad Radzi, Nur Hanis (Evolution in Electrical and Electronic Engineering, 2023)
Nowadays, students are not interested in STEM because they feel it is too difficult for them to understand it. One of the science syllabuses for primary and secondary school is the solar PV system. The student will face a problem in understanding how the solar PV system produces electricity without a hardware model. Thus, with the help of this project, people especially students can understand the solar PV system well and in addition can attract the student’s interest in STEM. This project aims to design and develop an educational kit of off-grid connected photovoltaic (OGPV) systems for residential houses. In this project, the total connected load, the maximum demand, and the maximum current for the residential house prototype model were determined before developing the complete educational kit model. Finally, the performance of the educational kit OGPV system for residential houses was evaluated. With the help of this project, the educator can easily deliver the content about the OGPV system effectively. This project also helps the students improve their understanding of this OGPV system.